2019
DOI: 10.1016/j.taap.2019.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Maternal titanium dioxide nanomaterial inhalation exposure compromises placental hemodynamics

Abstract: The fetal consequences of gestational engineered nanomaterial (ENM) exposure are unclear. The placenta is a barrier protecting the fetus and allowing transfer of substances from the maternal circulation. The purpose of this study was to determine the effects of maternal pulmonary titanium dioxide nanoparticle (nano-TiO 2) exposure on the placenta and umbilical vascular reactivity. We hypothesized that pulmonary nano-TiO 2 inhalation exposure increases placental vascular resistance and impairs umbilical vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
(34 reference statements)
4
25
0
Order By: Relevance
“…2e). Following an ENM exposure paradigm similar to the paradigm used for the current study, an increase in placental vascular resistance was reported, substantiating the antagonistic effects of nano-TiO 2 exposure during gestation [19]. Valentino et al further validate placental circulatory remodeling through a significant decline in placental flow in rabbits, which was observed following gestational exposure to diesel exhaust [54].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…2e). Following an ENM exposure paradigm similar to the paradigm used for the current study, an increase in placental vascular resistance was reported, substantiating the antagonistic effects of nano-TiO 2 exposure during gestation [19]. Valentino et al further validate placental circulatory remodeling through a significant decline in placental flow in rabbits, which was observed following gestational exposure to diesel exhaust [54].…”
Section: Discussionsupporting
confidence: 69%
“…2e). This effect may be occurring as a result of increased vascular resistance in the in utero circulation, which has been shown to reduce placental perfusion [19] and could increase the rate of perinatal mortality [49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal or intrauterine inflammatory pathways were also proposed to mediate developmental toxicity from exposure to air pollution [ 49 , 104 ] carbon black (CB) [ 17 , 101 ] and MWCNTs [ 100 ]. Besides inflammatory pathways, interference with the placenta (structure, growth or function/reactivity) has been suggested to constitute another indirect pathway for developmental toxicity of air pollution particles [ 104 ], cadmium telluride (CdTe) QDs [ 97 ], TiO 2 NP [ 96 ] in vivo or graphene oxide (GO) in vitro [ 103 ]. For prenatal exposure to CB, TiO 2 and CeO NPs (intratracheal instillation: 50 μg/mouse on GD 14), Fedulov et al observed increased allergic susceptibility in the offspring that was proposed to occur due to NM-induced production of Th2 cytokines in maternal lungs [ 102 ].…”
Section: Introductionmentioning
confidence: 99%
“…NO release plays a crucial role in maintaining the low basal tone of the materno-fetal circulation [ 169 ] and was therefore hypothesized to be implicated in the signaling causing the decrease in outflow pressure. Increased sensitivity to angiotensin II, a potent vasoconstrictor implicated in preeclampsia [ 170 ], was observed in both the placental and umbilical artery [ 96 ], also identifying the renin-angiotensin system as a perhaps crucial modulator of tissue tone.…”
Section: Introductionmentioning
confidence: 99%